2014
DOI: 10.1111/nph.12735
|View full text |Cite
|
Sign up to set email alerts
|

A miR169 isoform regulates specific NFYA targets and root architecture in Arabidopsis

Abstract: Summary In plants, roots are essential for water and nutrient acquisition. MicroRNAs (miRNAs) regulate their target mRNAs by transcript cleavage and/or inhibition of protein translation and are known as major post‐transcriptional regulators of various developmental pathways and stress responses. In Arabidopsis thaliana, four isoforms of miR169 are encoded by 14 different genes and target diverse mRNAs, encoding subunits A of the NF‐Y transcription factor complex. These miRNA isoforms and their targets have p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
148
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(149 citation statements)
references
References 82 publications
(131 reference statements)
1
148
0
Order By: Relevance
“…In Arabidopsis thaliana , overexpression of the closest homolog of MtNF-YA1, AtNF-YA2 leads to a significant increase in LR primordia density (Sorin et al, 2014) and the authors propose that AtNF-YA2 controls root architecture. Furthermore Laporte et al (2014) reported that MtNF-YA1 is also expressed transiently in LR primordia during LR initiation suggesting that this gene may also control LR growth in M. truncatula .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis thaliana , overexpression of the closest homolog of MtNF-YA1, AtNF-YA2 leads to a significant increase in LR primordia density (Sorin et al, 2014) and the authors propose that AtNF-YA2 controls root architecture. Furthermore Laporte et al (2014) reported that MtNF-YA1 is also expressed transiently in LR primordia during LR initiation suggesting that this gene may also control LR growth in M. truncatula .…”
Section: Discussionmentioning
confidence: 99%
“…This view is supported by the resistance triggered by miR169q overexpression in F83005.5 which is stronger than the one obtained via RNA interference. miR169 is encoded by a large gene family in plants (14 genes in Arabidopsis leading to four different mature miR169s ) and targets specifically the product of NF-YA genes with a certain degree of specificity (Sorin et al, 2014). It is thus likely that other NF-YA subunits such as MtNF-YA2 for example that is expressed in roots at a much higher level than MtNF-YA1 are targeted by the miR169q in M. truncatula and play overlapping functions with MtNF-YA1 in the susceptibility to A. euteiches .…”
Section: Discussionmentioning
confidence: 99%
“…Root hair curling and infection are also associated with changes in the microtubule cytoskeleton, and b-tubulins, which are cytoskeletal proteins, have been shown to be up-regulated in root hairs (Timmers, 2008;Breakspear et al, 2014; Perrine-Walker et al, 2014). We Sorin et al (2014). f De Smet et al (2008).…”
Section: Early Induction Of Genes Involved In Polar Root Hair Growthmentioning
confidence: 99%
“…It has been demonstrated that miR169/NFYA modules are important regulators of primary and lateral root development. For instance, expressing a miR169-resistant version of AtNFYA2 in Arabidopsis indirectly increased lateral root initiation and lateral root density but did not affect primary root growth (Sorin et al, 2014). However, the molecular mechanisms through which miR169/NFYA modules regulate root development are still not understood well.…”
mentioning
confidence: 99%